Health Communication in Mitigating The Risk of Physician and Controlling Covid-19 Outbreaks: A Qualitative Study on Emergency Department’s General Practitioners - Pramana, Hanif Prahita; Hastjarjo, Sri; Sudarmo, Sudarmo (JURNAL KOMUNIKASI INDONESIA, 2021)
As the front line of detection of patients infected with Covid-19, doctors have a high risk of transmission. However, doctors’ ability to provide proper communication with a unique medical interview process and persuasion of health context is needed. Patients can be open and honest about the illness symptoms and get the required information as prevention. This study aimed to determine doctor-patient communication changes and how information can reduce doctors’ risks of infection. Then, this research also aimed to know how the information from health communication to patients and their families can increase awareness toward the outbreak, change patients’ behavior, and likewise build a resilient society. As a qualitative case study, through semi-structured interviews with fourteen general practitioners of the Emergency Department and fourteen patients, we constructed some barriers and opportunities when doctors gave patients information about Covid-19 and figured out how it could be influence behavior. The attitudes and communication behaviors of doctors underwent several modifications, namely changes in the premedical examination, anamnesis, providing information, verification of information, and a tendency to change the relationship from mutualistic to paternalistic-informative. Provision of knowledge through information was carried out in a balanced way between risk and prevention so that patients behaved according to medical advice. Changes in community behavior indicated a difference in the community’s lifestyle, although it has not yet been consistent, to become a resilient, adaptive, and preventive community against pandemics. This paper provided findings for health communication value and offered useful suggestions for general practitioners, especially by educating vulnerable people during catastrophic events such as Covid-19.